NRT1.1 Dual-Affinity Nitrate Transport/Signalling and its Roles in Plant Abiotic Stress Resistance - Fang, Xian Zhi; Fang, Shu Qin; Ye, Zheng Qian; Liu, Dan; Zhao, Ke Li; Jin, Chong Wei (Frontiers in Plant Science, 2021)
NRT1.1 is the first nitrate transport protein cloned in plants and has both high- and low-affinity functions. It imports and senses nitrate, which is modulated by the phosphorylation on Thr101. Structural studies have revealed that the phosphorylation of T101 either induces dimer decoupling or increases structural flexibility within the membrane, thereby switching the NRT1.1 protein from a low- to high-affinity state. Further studies on the adaptive regulation of NRT1.1 in fluctuating nitrate conditions have shown that, at low nitrate concentrations, nitrate binding only at the high-affinity monomer initiates NRT1.1 dimer decoupling and priming of the T101 site for phosphorylation activated by CIPK23, which functions as a high-affinity nitrate transceptor. However, nitrate binding in both monomers retains the unmodified NRT1.1, maintaining the low-affinity mode. This NRT1.1-mediated nitrate signalling and transport may provide a key to improving the efficiency of plant nitrogen use. However, recent studies have revealed that NRT1.1 is extensively involved in plant tolerance of several adverse environmental conditions. In this context, we summarise the recent progress in the molecular mechanisms of NRT1.1 dual-affinity nitrate transport/signalling and focus on its expected and unexpected roles in plant abiotic stress resistance and their regulation processes.